A low complexity dynamic subarray combination method for MIMO transmitter - Cui WANG; Peng PAN; Shuai ZHANG; Junrong YAN (Dianxin kexue)
For the mmWave MIMO system using a partially-connected structure,in order to improve the spectral efficiency,the antenna composition of each subarray will be dynamically adjusted according to the channel conditions.However,the optimal grouping of antennas requires exhaustive searching for all possible antenna combinations according to certain criteri,which leads to unacceptable complexity.In response to the problem,a low-complexity sub-array dynamic allocation method was proposed.The core was to introduce certain rules when grouping array elements,thereby significantly reducing the number of combinations and reducing the search range.Specifically,two low-complexity antenna combination algorithms were proposed.Firstly,considering the strong correlation between mmWave antennas,multiple adjacent antennas were virtualized as an array element,thereby reducing the search space.Secondly,by dividing all antennas into upper and lower half areas,the antenna combination based on partition was realized,and the search space was also reduced.Simulation results show that the proposed method can achieve a good trade-off between performance and complexity.